SOCIAL RESTRICTIONS: MUJAHADAH AS A SPIRITUAL BRIDGE IN SUFISTIC ETHICS IN THE PANDEMIC ERA - Muhammad Amri; Risna Mosiba; Ahmad, La Ode Ismail (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This article discusses the social restrictions: mujahadah as a spiritual bridge in Sufistic ethics in the pandemic era. Some Muslim societies do not understand the Covid-19 pandemic, so they shut themselves and even refuse to make changes, especially in implementing worship. They believe in the loss of ethical aspects of religious teachings that they believe in because of trapped in fiqh-oriented dogmas and glued to jurisprudential texts so that they become exclusive and radical. Understanding and knowing human nature is a door to knowing oneself, life, the environment, nature, and God. If a man does not know himself, surely he will not know his God. Recognition and understanding of human nature require earnest mujahadah as a bridge for the establishment of religious qualities that balance esoteric and exoteric aspects. Humans are free social beings but limited by divine laws to maintain the authenticity of humanity. Social restrictions such as constitutional ijtihad that permeates the formal aspects of religion are a manifestation so that humans remain ihsan to themselves, others, and their environment. The Covid-19 pandemic is a love letter from God as the holy verses revealed to the Prophet Muhammad as a warning because humans have been separated from the cycling of other orbits, namely God and nature. Social restrictions as constitutional ijtihad are the right moment for humans to return to greet God, themselves, nature, and khuruj from a materialistic vision of life.